2023
DOI: 10.35877/454ri.qems2158
|View full text |Cite
|
Sign up to set email alerts
|

Compensation, Worklife Balance, Employee Engagement, and Turnover Intention

Ni Nyoman Triningsih,
Gede Sri Darma

Abstract: The significance of conducting this study lies in its pressing relevance to PT Bali Busana Kreasi, aiming to address turnover intention issues and foster a more productive and fulfilling work environment for its employees. The study's core objective is to scrutinize the impact of compensation and work-life balance on turnover intention, with employee engagement serving as a mediating factor. This research employs a quantitative research approach and is conducted at PT Bali Busana Kreasi, situated on Jl Raya An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…More proof of the inverse association between engagement and the desire to quit, the study found that engagement significantly affects turnover intention. Triningsih and Darma (2023) looked studied the relationship between PT Bali Busana Kreasi employees' intentions to leave and factors including pay, work-life balance, and engagement. Pay and work-life balance were found to have significant negative impacts on the desire to leave an organization.…”
Section: Employee Engagement and Turnover Intention Among Employeesmentioning
confidence: 99%
“…More proof of the inverse association between engagement and the desire to quit, the study found that engagement significantly affects turnover intention. Triningsih and Darma (2023) looked studied the relationship between PT Bali Busana Kreasi employees' intentions to leave and factors including pay, work-life balance, and engagement. Pay and work-life balance were found to have significant negative impacts on the desire to leave an organization.…”
Section: Employee Engagement and Turnover Intention Among Employeesmentioning
confidence: 99%